PENERAPAN MODEL PEMBELAJARAN KOOPERATIF THINK PAIR SHARE TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS XI SMAN 4 SUMATERA BARAT - Fauzannisa, Saphira (Departemen Matematika, 2025)
It is essential for students to have the ability to understand mathematical concepts. As this is the most fundamental level of cognition, mastering it is a prerequisite for developing other skills. However, this is still at a low level at SMAN 4 West Sumatra. Applying the cooperative learning model of think-pair-share (TPS) type is one way to overcome this. In class XI of SMAN 4 West Sumatra, the TPS model was used to see if it could improve students' understanding of mathematical topics compared to the traditional learning model. This study used a quasi experimental with posttest-only control group design. Students from class XI F2 and XI F3 in eleventh grade at SMAN 4 in West Sumatra became the population of this study. According to the data, the class average in the experimental group was greater than the control group. So it can be concluded that TPS provides better knowledge of mathematical concepts compared to the conventional model, because the alternative hypothesis is accepted and the P-value is smaller than α.Keywords– Mathematical Concept Understanding, Think Pair Share Model, Conventional Learning Model